Microseismicity in the period 12/2018-01/2019 at the southern Fonualei Rift and Spreading Center, Lau Basin, with SEISAN waveform files and traveltime picks - Florian Schmid; Heidrun Kopp (PANGAEA, 2021)
This dataset includes earthuake location results from a 32-days long Ocean Bottom Seismometer (OBS) experiment conducted at the southern end of the Fonualei Rift and Spreading Center in the Lau Basin, southwestern Pacific. The experiment was conducted during RV Sonne cruise SO267, project ARCHIMEDES I. The accompanying zip-file "SEISAN_files.zip" includes raw waveform data for all earthquakes and the file "select.out" that includes all manual phase onset picks of all earthquakes. All data in the zipped archive "SEISAN_files.zip" may be processed and used with the SEISAN seismology software.